Developing Essential Understanding of Functions for Teaching Mathematics in Grades 9-12 - Cooney, Thomas J., ....-; Beckmann, Sybilla, ....-; Lloyd, Gwendolyn M., ....-; Wilson, Patricia S., ....- (National Council of Teachers of Mathematics : Reston, 2014)
Are sequences functions? Why can't the popular “vertical line test” be applied in some cases to determine if a relation is a function? How does the idea of rate of change connect with simpler ideas about proportionality as well as more advanced topics in calculus? How much do you know… and how much do you need to know? Helping your high school students develop a robust understanding of functions requires that you understand mathematics deeply. But what does that mean? This book focuses on essential knowledge for teachers about functions. It is organized around five big ideas, supported by multiple smaller, interconnected ideas—essential understandings. Taking you beyond a simple introduction to functions, this book will broaden and deepen your mathematical understanding of one of the most challenging topics for students—and teachers. It will help you engage your students, anticipate their perplexities, avoid pitfalls, and dispel misconceptions. You will also learn to develop appropriate tasks, techniques, and tools for assessing students' understanding of the topic. Focus on the ideas that you need to understand thoroughly to teach confidently.
Keywords: Functies (wiskunde).